Analisis Konflik Pabrik Semen di Rembang dalam Perspektif Johan Galtung - Sidik Puryanto (PERSPEKTIF, 2023)
This study aims to analyze the conflict between the cement factory in Rembang using the Galtung perspective. Galtung's theory includes three concepts, namely contradiction, attitude and behavior. The setting of this research is in Gunem District, Rembang Regency. This study uses a qualitative approach, the type of case study method. The data collection process was carried out by interviewing 20 people. The interview process was carried out when the cement factory conflict was at its done on the top in 2017-2020. The conflict was still real, because it has widened into an ideological conflict. The results of this study indicate that the main issue underlying the conflict was the local government's policy of granting a permit for the exploitation of a cement factory in Gunem Tegaldowo. The dominant policy in the economic context, is not proportional to the impact of damage to nature and the environment, where people farm and meet their water needs. The dominance of economic policy leads to (1) different perceptions, (2) people's hatred towards the government, and creates contradictions by making various efforts to refuse. The actions are carried out in 3 categories (1) questioning behavior, (2) opposing behavior, (3) protest behavior. Cement factory conflicts are different from communal conflicts. Cement factory conflicts are closely related to political policies made by government officials who have interests. The cement factory conflict is a conflict algorithm or conflict by design.